Circulating Endothelial Cells as Promising Biomarkers in the Differential Diagnosis of Primary Angiitis of the Central Nervous System - Deb-Chatterji, Milani; Pinnschmidt, Hans Otto; Duan, Yinghui; Haeussler, Vivien; Rissiek, Björn; Gerloff, Christian; Thomalla, Götz; Magnus, Tim (Frontiers in Neurology, 2020)
Background: Diagnosis of primary angiitis of the central nervous system (PACNS) and discrimination of PACNS from its mimics, e.g. reversible cerebral vasoconstriction syndrome (RCVS) or moyamoya disease (MMD) as non-inflammatory vasculopathies, still remain challenging. Circulating endothelial cells (CEC) are well-established markers for endothelial damage and potential biomarkers in PACNS. This study aimed to investigate if CECs may also help to distinguish an active PACNS from its important differentials (RCVS, MMD). Methods: CECs were assessed in 47 subjects. Twenty-seven patients with PACNS were included, seven with an active disease (aPACNS), 20 in remission (rPACNS). Seven patients with RCVS/MMD were analyzed. Thirteen healthy subjects served as controls (HC). CECs were measured by immunomagnetic isolation from peripheral venous blood. Mann-Whitney-U-Tests were applied for between-group comparisons. The Benjamini-Hochberg-procedure was applied to adjust for multiple comparisons. Results: In aPACNS, CECs were significantly elevated compared to HC (480 CEC/ml vs. 40 CEC/ml, p<0.001) and rPACNS (54 CEC/ml, p<0.001). RCVS/MMD patients showed higher CEC levels (288 CEC/ml) than HC (p<0.001), but lower than those in aPACNS (p=0.017). An adjustment for multiple comparisons confirmed prior significant differences. An increased CEC value (cutoff 294 CEC/ml) is indicative for an active PACNS (sensitivity 100%, 95% confidence interval (CI) 63-100%; specificity 93%, CI 81-98%). Conclusions: CECs may serve as biomarkers for diagnosis, treatment monitoring and also for differential diagnosis of PACNS. CECs seem to be a marker of endothelial injury with higher levels in inflammatory than non-inflammatory vasculopathies. Larger patient samples are required to corroborate these findings.